Dysregulation of Systemic Immunity in Aging and Dementia - Lutshumba, Jenny; Nikolajczyk, Barbara S.; Bachstetter, Adam D. (Frontiers in Cellular Neuroscience, 2021)
Neuroinflammation and the tissue-resident innate immune cells, the microglia, respond and contribute to neurodegenerative pathology. Although microglia have been the focus of work linking neuroinflammation and associated dementias like Alzheimer’s Disease, the inflammatory milieu of brain is a conglomerate of cross-talk amongst microglia, systemic immune cells and soluble mediators like cytokines. Age-related changes in the inflammatory profile at the levels of both the brain and periphery are largely orchestrated by immune system cells. Strong evidence indicates that both innate and adaptive immune cells, the latter including T cells and B cells, contribute to chronic neuroinflammation and thus dementia. Neurodegenerative hallmarks coupled with more traditional immune system stimuli like infection or injury likely combine to trigger and maintain persistent microglial and thus brain inflammation. This review summarizes age-related changes in immune cell function, with special emphasis on lymphocytes as a source of inflammation, and discusses how such changes may potentiate both systemic and central nervous system inflammation to culminate in dementia. We recap the understudied area of AD-associated changes in systemic lymphocytes in greater detail to provide a unifying perspective of inflammation-fueled dementia, with an eye toward evidence of two-way communication between the brain parenchyma and blood immune cells. We focused our review on human subjects studies, adding key data from animal models as relevant.